(untitled) (Conference Zone, 2022)
In modern society, attention to family problems has increased significantly. This situation is the problem of motherhood and childhood, the increase in the number of dysfunctional families, the rapidly increasing number of children with psychophysical developmental disabilities, the problems of social support for orphans, the increasing complexity of the emotional and spiritual world of a modern person, and the socio-economic and socio-cultural aspects of society. conditioned by problems.